Service Orientation of Manufacturing Companies in The Context of Industry 4.0 - Mirosław MATUSEK (Communications of International Proceedings, 2021)
The aim of this research was to find the technologies that make up Industry 4.0, which are characteristic of each of the three adopted types of service orientation of manufacturing enterprises. Service orientation, servitization and infusion of digital technologies in manufacturing enterprises have until recently been studied in their partial isolation. The convergence of these phenomena appears in the literature under the name of digital servitisation. The authors emphasise the need for a more focused research effort to better understand the phenomenon of digital servitisation. One of the challenges is to explain how the digital technologies that make up Industry 4.0 support the servitization and service orientation of manufacturing enterprises. The research was conducted on a group of 280 Polish manufacturing enterprises of the SME sector using the cluster analysis method.
Keywords: Industry 4.0; service orientation; servitisation; services